TUBERCULOSIS BEYOND THE ORDINARY: A CASE SERIES INVESTIGATING PULMONARY AND EXTRA-PULMONARY PRESENTATIONS - KUNJAN PARESHKUMAR SHAH,; PANDYA DHRUVKUMAR JITENDRAKUMAR,; DEVANSHKUMAR PATEL, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Despite advancements in diagnostic modalities and treatment strategies, diagnosing and managing atypical cases of pulmonary and EPTB, which can affect multiple organ systems, present unique challenges. We present a case series highlighting diverse presentations of TB, emphasizing diagnostic dilemmas and management approaches. Methods: We conducted a retrospective analysis of patients diagnosed with Tuberculosis at our tertiary care center over a specified period. Clinical presentations, diagnostic evaluations, treatment regimens, and outcomes were systematically reviewed. Results: We present seven cases illustrating the heterogeneity of TB manifestations. These include tuberculosis of the pleura, tuberculoma, bone marrow tuberculosis and metastasis. Each case presented distinct diagnostic challenges, such as differentiating TB from other pathologies and identifying suitable diagnostic modalities. Management strategies involved anti-tubercular therapy tailored to the site and extent of disease, often supplemented by adjunctive measures. Conclusion: Our case series underscores the varied clinical presentations and diagnostic complexities of pulmonary and EPTB. Early recognition, a high index of suspicion, and multimodal diagnostic approaches are crucial for timely initiation of appropriate treatment. Further research is warranted to elucidate optimal diagnostic algorithms and therapeutic interventions for pulmonary and EPTB, particularly in resource-limited settings.